Achalasia of the Cardia in a 21 Year old Pregnant Lady: A Case Report (Tanzania Medical Journal, 2009)
Achalasia of the cardia is a motor disorder of the lower oesophagus of unknown aetiology. It is characterized by persistent dysphagia in 82 – 100% of patients. We describe a rare case of dysphagia due to Achalasia cardia in a pregnant lady in her third trimester. Tanzania Medical Journal Vol. 23 (2) 2008: pp. 31-32